A gest??o do Programa de Descentraliza????o Administrativa e Financeira (PDAF) e seu resultado na autonomia e na democratiza????o - Trindade, Ros??ngela Rodrigues (2015)
This research analyzes the management of the Administrative and Financial Decentralization Program (AFDP) in the Federal District. The study had as main objective, identify and analyze the limits and possibilities of the autonomy and democratic management of funds from (AFDP), in a public high school from the DF, in the period of 2011 to 2014. Therefore, the qualitative methodology was adopted with an exploratory study. According to the research, a case study was constituted. It was used as data collection techniques in documentary research, observations and semi-structured interviews. The data analysis was done through content analysis method. The research took as its starting point the analysis of documents related to school organization, such as their Pedagogical Political Project and the school census data from the years 2011-2014, as well as the analysis of financial documents and paychecks of the programs. The second stage was carried out through interviews with school managers and 07 (seven) representatives of the School Board of the institution, As well as two representatives of the performing unit of AFDP in the school and the head chief of the resource decentralization core of the Federal District Secretary of Education. The literature review considered the issues related to the funding of education in Brazil, the educational policies of financial decentralization, administrative and financial autonomy and democratic management of public schools. As a result, the research showed that school autonomy is possible and AFDP helps it to perform in the administrative and financial aspects, which ultimately reflect in the pedagogical area. It is a relative autonomy, since public schools are part of a larger system both locally and nationally. However, the limits indicated in the survey relate to such factors as the allocation of resources, delays in transfers, failure to disclose the amounts for school even in the previous year, the lack of these resources to meet all the needs and bureaucracy accountability. As the consolidation of democratic management research has shown, the autonomy helps, but it is not a synonymous of democracy. For this to be fully accomplished, those involved in the process has to take ownership of their rights, as the law establishes it. The school needs the involvement of everyone, so it is considered that democratic management is also part of a process in formation